Prevention of Incisional Hernias with Biological Mesh: A Systematic Review of the Literature - Muysoms, Filip E.; Jairam, An; López-Cano, Manuel; Śmietański, Maciej; Woeste, Guido; Kyle-Leinhase, Iris; Antoniou, Stavros A.; Köckerling, Ferdinand; , BioMesh Study Group; Köckerling, Ferdinand; Antoniou, Stavros; Fortelny, René; et al. (Frontiers in Surgery, 2016)
Background: Prophylactic mesh augmented reinforcement during closure of abdominal wall incisions has been proposed in patients with increased risk for development of incisional hernias (IH). As part of the BioMesh consensus project, a systematic literature review has been performed to detect those studies where MAR was performed with a non-permanent absorbable mesh (biological or biosynthetic). Methods: A computerized search was performed within 12 databases (Embase, Medline, Web-of-Science, Scopus, Cochrane, CINAHL, Pubmed publisher, Lilacs, Scielo, ScienceDirect, ProQuest, Google scholar) with appropriate search terms. Qualitative evaluation was performed using the MINORS score for cohort studies and the Jadad score for RCTs. Results: For midline laparotomy incisions and stoma reversal wounds, 2 RCTs, 2 case control studies and 2 case series were identified. The studies were very heterogeneous in terms of mesh configuration (cross linked versus non cross linked), mesh position (intraperitoneal versus retromuscular versus onlay), surgical indication (gastric bypass versus aortic aneurysm), outcome results (effective versus non effective). After qualitative assessment we have to conclude that the level of evidence on the efficacy and safety of biological meshes for prevention of incisional hernias is very low. No comparative studies were found comparing biological mesh with synthetic non-absorbable meshes for the prevention of incisional hernias. Conclusion: There is no evidence supporting the use of non-permanent absorbable mesh (biological or biosynthetic) for prevention of incisional hernias when closing a laparotomy in high-risk patients or in stoma reversal wounds. There is no evidence that a non-permanent absorbable mesh should be preferred to synthetic non-absorbable mesh both in clean or clean-contaminated surgery.